Auditory change-related cerebral responses and personality traits. (February 2016) - Tanahashi, Megumi; Motomura, Eishi; Inui, Koji; Ohoyama, Keiko; Tanii, Hisashi; Konishi, Yoshiaki; Shiroyama, Takashi; Nishihara, Makoto; Kakigi, Ryusuke; Okada, Motohiro
Highlights: The sensitivity of cerebral change detection is inherent in individuals. Change-N1 on evoked potential reveals the sensitivity of this cerebral system. We aim to clarify the relationship between Change-N1 and personality traits. Anxiety- and depressive-personality might affect change detection system. Abstract: The rapid detection of changes in sensory information is an essential process for survival. Individual humans are thought to have their own intrinsic preattentive responsiveness to sensory changes. Here we sought to determine the relationship between auditory change-related responses and personality traits, using event-related potentials. A change-related response peaking at approximately 120 ms (Change-N1) was elicited by an abrupt decrease in sound pressure (10 dB) from the baseline (60 dB) of a continuous sound. Sixty-three healthy volunteers (14 females and 49 males) were recruited and were assessed by the Temperament and Character Inventory (TCI) for personality traits. We investigated the relationship between Change-N1 values (amplitude and latency) and each TCI dimension. The Change-N1 amplitude was positively correlated with harm avoidance scores and negatively correlated with the self-directedness scores, but not with other TCI dimensions. Since these two TCI dimensions are associated with anxiety disorders and depression, it is possible that the change-related response is affected by personality traits, particularly anxiety- or depression-related traits.